THE CONTENS OF HEAVY METALS (Pb, Cu, AND Zn) IN MANGROVE SNAIL (Nerita lineata) FROM THE WEST COAST OF KARIMUN ISLANDS RIAU ARCHIPELAGO PROVINCE - Desi Purnama Sari; Yusni Ikhwan Siregar; Bintal Amin (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
The research was conducted in February 2015 with the aim to analyze andcompare the contents of Pb, Cu and Zn in soft tissue and shells of the mangrovesnail (Nerita lineata) from three stations with different activities. The researchwas also objected to analyze the consumption feasibility of the snail as well as tounderstand the status of metal pollution by calculating the value of MPI (MetalPollution Index). The results showed that the average Pb content (8.197 and 8.538μg/g) of snails was greater than Zn (6.992 and 7.718 μg/g) and Cu (4.614 and4.468 μg/g) for soft tissue and shells respectively. Metal Pollution Index valuewas 6.552 indicated that the pollution status in the coastal waters of the west coastof Karimun Besar Island Riau Archipelago Province was still relatively low. Themangrove snail from this coastal waters were also considered safe forconsumption as long as not exceeding the limit of 0.836 kg/week based on Pb,208.68 kg/week based on Cu and 298.23 kg/week based on Zn concentrations.Key Words: Heavy metal, Mangrove snail, Nerita lineata, Karimun Islands.